Activation of Biodefense System by Low-Dose Irradiation or Radon Inhalation and Its Applicable Possibility for Treatment of Diabetes and Hepatopathy. (9th February 2012) - Kataoka, Takahiro; Yamaoka, Kiyonori
Abstract : Adequate oxygen stress induced by low-dose irradiation activates biodefense system, such as induction of the synthesis of superoxide dismutase (SOD) and glutathione peroxidase. We studied the possibility for alleviation of oxidative damage, such as diabetes and nonalcoholic liver disease. Results show that low-dose γ -irradiation increases SOD activity and protects against alloxan diabetes. Prior or post-low-dose X- or γ -irradiation increases antioxidative functions in livers and inhibits ferric nitrilotriacetate and carbon tetrachloride-induced (CCl4 ) hepatopathy. Moreover, radon inhalation also inhibits CCl4 -induced hepatopathy. It is highly possible that low-dose irradiation including radon inhalation activates the biodefence systems and, therefore, contributes to preventing or reducing reactive oxygen species-related diabetes and nonalcoholic liver disease, which are thought to involve peroxidation.